Up your productivity - Hanks, Kurt (Crisp Pub. Menlo ParkUS, 1990)
Analyses several management problems/issues and suggests methodologies for dealing with them. Topics addressed include: three steps toward change; biting off more than you can chew; efficiency v. effectiveness; giving praise; guide to performance appraisal and job requirements; hiring the right persons initially; Murphy's law and the Murphy cushion; overspecializing on specialists; promotion; time management; thirty-nine proven principles for increasing productivity.